The multicast multimedia conference recorder - Lambrinos, Lambros; Kirstein, Peter; Hardman, Vicky (My University, 1998)
© 1998 IEEE. The ability to archive multimedia data is required in most applications of multimedia conferencing. This paper describes the generic client-server architecture of a multicast multimedia server system and the design and implementation of the multicast multimedia conference recorder (MMCR). The MMCR is a remotely controlled system capable of recording and playing back multimedia data over the MBone. It has a client-server architecture and the logical independence between components simplifies development and component replication. The MMCR uses indexes to facilitate fast data access, allowing efficient fast-forward, rewind and random access operations. Inter-stream synchronisation between recorded audio-video streams is improved by eliminating the network delay variance.
Keywords: Teaching; E-learning; Video conferencing